Population Ageing and Productivity: Implications and Policy Options for New Zealand - Ross Guest (New Zealand Government, The Treasury, 2013)
This paper critically evaluates the effects of population ageing on labour productivity with particular reference to New Zealand. A number of potential long run mechanisms are considered: complementarity of workers by age, age-specific productivity of individuals, new technology discoveries and adoptions, fertility and human capital investments. Potential short run channels include: the `second demographic dividend', changes in industry composition, incentives to seek labour saving technologies. Simulations tentatively suggest that workers could become more complimentary by age which would boost labour productivity. The magnitude of this effect on living standards could entirely offset the projected 12 per cent fall in the support ratio over the next 40 years. The most effective policies for mitigating the national economic burden of ageing are policies to boost labour participation of older workers and to boost immigration.
Keywords: J11; E20; E62; 330; Population ageing; labour productivity; demographic dividend